Penyelenggaraan Kegiatan (Event) Berbasis CHSE Pada Program Vaksinasi Pekerja Pariwisata Di Hotel Grand Hyatt Bali - Nelsye Lumanauw; I Gst. Bgs. Wirya Gupta (UNHI Press, 2022)
In the midst of the Covid-19 pandemic, the implementation of a vaccination program can still be arranged on a strict CHSE-based, to prevent and control the spread of Covid-19. The tourism recovery has been being focused on accelerating the economic growth in Bali, therefore tourism workers have got priority to receive vaccines. The purpose of this study was to evaluate the CHSE implementation of a vaccination program for tourism workers at the Grand Hyatt Bali Hotel. This research uses the descriptive analysis method by collecting data at pre-event, on-event, post-event based on the concept and theory of event management, health protocols, new normal, and vaccination, through interviews and direct observation at the location. The conclusion is, there have been various negligence and indiscipline by both officers and participants who received the vaccine. The suggestion for event organizers is, it is a must to ensure the CHSE health protocol is implemented at pre-event, on-event, post-event.